Different Imaging Strategies in Patients With Possible Basilar Artery Occlusion. Issue 7 (July 2015) - Beyer, Sebastian E.; Hunink, Myriam G.; Schöberl, Florian; von Baumgarten, Louisa; Petersen, Steffen E.; Dichgans, Martin; Janssen, Hendrik; Ertl-Wagner, Birgit; Reiser, Maximilian F.; Sommer, Wieland H.
<x xml:space="preserve">Abstract</x> Background and Purpose— This study evaluated the cost-effectiveness of different noninvasive imaging strategies in patients with possible basilar artery occlusion. Methods— A Markov decision analytic model was used to evaluate long-term outcomes resulting from strategies using computed tomographic angiography (CTA), magnetic resonance imaging, nonenhanced CT, or duplex ultrasound with intravenous (IV) thrombolysis being administered after positive findings. The analysis was performed from the societal perspective based on US recommendations. Input parameters were derived from the literature. Costs were obtained from United States costing sources and published literature. Outcomes were lifetime costs, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratios, and net monetary benefits, with a willingness-to-pay threshold of $80 000 per QALY. The strategy with the highest net monetary benefit was considered the most cost-effective. Extensive deterministic and probabilistic sensitivity analyses were performed to explore the effect of varying parameter values. Results— In the reference case analysis, CTA dominated all other imaging strategies. CTA yielded 0.02 QALYs more than magnetic resonance imaging and 0.04 QALYs more than duplex ultrasound followed by CTA. At a willingness-to-pay threshold of $80 000 per QALY, CTA yielded the highest net monetary benefits. The probability that CTA is cost-effective was 96% at a willingness-to-pay threshold of $80 000/QALY. Sensitivity analyses showed that duplex ultrasound was cost-effective only for a prior probability of ⩽0.02 and that these results were only minimally influenced by duplex ultrasound sensitivity and specificity. Nonenhanced CT and magnetic resonance imaging never became the most cost-effective strategy. Conclusions— Our results suggest that CTA in patients with possible basilar artery occlusion is cost-effective.